AN IN VITRO ESTIMATION OF CYTOTOXICITY OF FUSARIUM TRICHOTHECENE ON THE BREAST CANCER CELL LINE - Rin. S. Mukhammadiev; Rish. S. Mukhammadiev; V. V. Biryulya; I. I. Idiyatov; A. A. Nabatov; A. P. Glinushkin; L. R. Valiullin (Сибирский онкологический журнал)
trichothecenes and their derivatives have recently attracted much attention of researchers with respect of their potential role in medicine, including for the treatment of different types of cancer. The purpose of the study was to investigate the cytotoxic effect of Fusarium trichothecene on human breast cancer cells,  human skin fibroblasts and embryonic kidney cells in vitro. Material and methods. Based on the Mtt assay, the cytotoxic effect of trichothecene on cell cultures was determined. Evaluation of morphological changes in cell cultures under the influence of trichothecene was performed by light microscopy. Results. Fusarium trichothecene was found to exhibit a dose-dependent toxic effect on cell lines in the range 1 nM to 1000 nM. the most pronounced cytotoxic effect of trichothecene was observed in human breast cancer cell line (IС50 94.72 ± 4.1 нМ). Lower doses of trichothecene led to a change in the size, shape of human breast cancer cells, human skin fibroblasts and embryonic kidney cells, and loss of contact between them and their isolation. the degradation of cell membranes, formation of unformed cell aggregates and fragments were observed in higher doses of trichothecene. Conclusion. Fusarium trichothecen is a biologically active compound and is less toxic to the normal than to the cancer cell lines, therefore, further studies of this agent are needed.